Should Our Kindergartens and Schools be Electronic Media Free Zones? - Goldshmidt, Gilad (American Journal of Education and Learning, 2018)
This article raises the question of the place of media in educational institutions. Various media formats from the surrounding, general culture are integrated naturally into kindergartens and schools. Schools have always reflected the spirit of their time and culture and the question of media is no different. This article examines another path. A path of resistance and of creating an opposing culture. First, I will examine the position of each one of us, the adult individual, with regard to screen technology, then I will look closely at the relations between the young child and screen culture, and at child development and its relationship to the issue of screen technology. Finally, I will attempt to show that educational processes and institutions should, fittingly, be media-free safe spaces.